Design and implementation of radio frequency identification system - Zhang, Shaoliang (2013)
The adoption rate of Radio Frequency Identification (RFID) technology has been increasing over recent decades. In this project, several main challenges were addressed in order to achieve even higher market adoption. We focused our attention on research in: RFID power transmission efficiency development, power transition circuits and information transmission techniques. We designed and simulated an RFID circuit with resonant frequency of 13.56 MHz by LTSpice software. Based on the design we implemented and tested the RFID system prototype to make sure it has equipped the full functionalities. At the end of the project we conclude by suggesting the future work on more areas which need to be improved.